منزلة أُولِي العَزمِ من الرّسل في حياتهم الاجتماعية من خلال القرآن والسنة - Ananda, Fadhli; Gasmelsid, Saadeldin Mansour Gasmelsid (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2025)
This study aims to highlight the significance of social life from the perspective of the Qur'an and Sunnah by focusing on the practical examples set by the Ulū al-ʿAzm messengers. Their stories were chosen due to the profound lessons and noble values they offer, which remain relevant to the social life of humanity. The research adopts a descriptive-analytical method with a thematic approach to selected Qur'anic verses and Prophetic traditions, supported by classical tafsir works, hadith commentaries, and Islamic educational literature. One of the central findings is that the Qur'an and Sunnah emphasize the importance of adhering to the community (jamaʿah), which yields significant benefits such as protection from misguidance, safeguarding of the heart, the descent of divine mercy, and the realization of shari'ah objectives within society. The study also concludes that the Ulū al-ʿAzm messengers occupy an exceptional status and possess great virtues, as they are leaders of the faith, chosen ones among nations, exemplary role models, and intercessors for humanity on the Day of Judgment.